The effect of firm characteristics on earnings management practices among Malaysian public listed companies in the technological industry / Erlane K Ghani, Nur Afifah Mohd Azemi and Evita Puspitasari - Ghani, Erlane K; Mohd Azemi, Nur Afifah; Puspitasari, Evita (Universiti Teknologi MARA Cawangan Selangor, 2019)
This study investigated the effect of firm characteristics on earnings management practices among technology-based public listed companies in Malaysia. Specifically, this study examined the effect of firm size, firm profitability and firm leverage on the companies’ practices of earnings management. Using 83 technology-based companies listed in the FTSE Bursa Malaysia KLCI Index for 2015 and 2016, this study showed a statistically positive relationship between firm size and earnings management practices. Such a finding indicates that larger companies tend to use earnings management incentives to enhance their performance. However, firm profitability and firm leverage have no significant relationship to the occurrence of earnings management practices. This study provides evidence that firm size influences the occurrence of earnings management among Malaysian public listed companies in the technological industry.